The Arden Grating Test of Visual Function - Feeley, Helen Kalish (Canadian Journal of Optometry, 1980)
In the absence of detectable pathology, the optometrist must ascertain why a reading of 6/6 Snellen is not achieved. A new, inexpensive and simple test has been developed for this purpose, useful even with illiterates. An explanation of the test, some of its applications and drawbacks, plus comparison with other, currently used tests is presented.